A gestão de tributos nas sociedades em forma de consórcio em São Luis do Maranhão - Pires, Maria Edwige dos Santos (2010)
Companies as a consortium are characterized as an important strategic alliance, being allowed shared production and costs an incomes sharing. That attribute, however, does not exclude them from the Brazilian Tax System rules and regulations, therefore they go after minimizing the effect of this duty in the result of the company through techniques to reduce, extinct and postpone tax costs on their activities, no matter if they are of conformity, direct or indirect. This technique is called tax management. Thus, the most important objective associated with this theme is to evaluate the contribution of tax management in companies that work as a consortium in São Luis of Maranhão. For the success purpose of this work, it was performed a study of descriptive nature based on primary and secondary data related to concepts, classifications, several interpretations and simulations about tax management, besides the use of data collecting tools such as questionnaires and semi-structured interviews applied to selected companies. The results show that tax management in companies as a consortium in São Luis, Maranhão does not yet cover the three species, mainly the most complex kind of management, Tax Planning. The survey also demonstrated that tax management is intrinsically related to the enterprise execution deadline and its mission.